O cinema nos filmes de David Lynch: uma análise sobre a reflexividade e mise en abyme em Mulholland Drive e Inland Empire - Góes, Alan Eduardo dos Santos (2016)
This study aims to analyze the agency modes of reflective films proposed by the north-american artist David Lynch, with greater attention to both movies Mulholland Drive and Inland Empire. Besides, some discussions will be redeemed on cinematic apparatus, since its conceptual proposition by Baudry, through updates as proposed by Metz and some recent notions such as those presented by André Parente. The outlook on the cinematic apparatus are related to the concepts of mise en abyme, operated by André Gide and subsequently developed by Dällenbach, and applied to the films of David Lynch by the work of Fatima Chinita; and the metacinematographic reflectivity and metafilmic reflectivity, presented by Metz, as well. It will present another issues that orbit the filmography of the director and researches on the topic oftenly, namely: the dispossession of artistic languages, conflicts between a genre cinema and an independent film and the surrealistic art movement. These discussions help us to understand some secondary traits of our research that pervade both the trajectory of the author as the films under our observation. The analyze of both movies are based on the routes listed above and, where possible, articulated with transdisciplinary thoughts that allow us to explore specific aspects, especially with cyberculture, studies of film theory and psychoanalysis. The relationship of these different theoretical perspectives endow the artifices to deepen narrative, technical and aesthetic instances of Mulholland Drive and Inland Empire. The management of those aspects apparently fragmented, in theory and in the works of the north-american filmmaker, are reflected in the structure of this work, with noncumulative and non-sequential chapters for each treated subject. Finally, the conceptual operations proposed to analyze the chosen corpus of moving images allow us to defend that reflectivity is a structural element in the David Lynch film works and, in general, in some parts of contemporary cinema.